Когнітивне та комунікативно-прагматичне розуміння інтимізації - Палійчук, Анна Леонардівна; Paliychuk, Anna (Східноєвропейський національний університет імені Лесі Українки, 2013)
Стаття представляє інтегрований когнітивний та комунікативно-прагматичний підхід до розуміння інтимізації у художньому дискурсі. Проаналізовано низку існуючих визначень інтимізації з позицій дискурсивної лінгвістики. Здійснено аналіз концепту ІНТИМІЗАЦІЯ / PROCESS/RESULT OF BEING INTIMATE.The article presents an integrated cognitive and communicative-pragmatic approach to the understanding of intimization. A number of existent discourse linguistic definitions of intimization are considered. The concept ІНТИМІЗАЦІЯ / PROCESS/RESULT OF BEING INTIMATE is analyzed, three hypersemes are singled out - friendliness, closeness/short distance, disclosure/frankness. Intimization is treated as a communicative strategy and is implemented by means of a number of tactics, that create an effect of closeness, friendliness and direct emotional communication with a reader. They imitate oral conversation and cause the illusion of real, synchronous artistic communication.
Cognitive and Communicative-pragmatic Understanding of Intimization
Keywords: дискурс; інтимізація; комунікативна стратегія; концепт; discourse; intimization; communicative strategy; concept